A hybrid method for information technology selection combining multi-criteria decision making (MCDM) with technology roadmapping (2013)
Abstract: Strategic information technology (IT) management has been recognized as vital for achieving competitive advantage. IT selection, the process of choosing the best technology alternative from a number of available options, is an important part of IT management. The IT selection is a multi-criteria decision making process, where relative importance of each criterion is determined and the degree of satisfaction of every criterion from each alternative is evaluated. Decision makers (DMs) face several difficulties like making precise judgements about alternatives and criteria, reaching consensus with other DMs and identifying relative criteria importance where there is interdependence among them. Actual environment has even increased this complexity, IT is constantly changing over time, new features and quality improvements are released periodically. At the same time, DMs' needs evolve after technology acquisition, demanding also new functionalities. For dealing with these factors, DMs should review not only the present state of their requirements and alternatives but their future evolution. Several methods have been proposed for dealing with the criteria interdependence, imprecision and group consensus problems. However, none of them have considered alternatives and criteria evolution in time. This research aims to review how the described problem is handle in the literature and based on the results of the review, to provide a methodology which handle all described problems simultaneously, by the combination of technology roadmapping technique with multi-criteria decision making tools. Finally, a case study of a customer relationship management (CRM) system selection is presented where the approach is compared with a one period one. It is concluded that the use of the methodology allows DMs to gather present and future requirements for IT selection, to consider actual and future evolution of alternatives, to determine and to establish relative importance among present and future factors. It is also detected how the judgement combination, experts consistency and performing methodology calculations are the critical topics for getting the best result in the methodology application.